(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This study analyzes the coverage of environmental problems in Kyrgyzstan within mass media. It examines the importance, functions, and characteristics of environmental journalism. The study analyzes the current state of environmental journalism in Kyrgyzstan, including the role of media resources and information publications. It also proposes problems hindering the development of this sector and ways to solve them. The study emphasizes the important role of environmental journalism in addressing environmental problems in Kyrgyzstan and the necessity of joint efforts by the state, media resources, and society for its development.